Implementation of numerical-computational tools for fluid-structure interaction analysis in industrial cases - Oliveira, Gabriel Sabino de (2025)
Fluid-Structure Interaction (FSI) is a multiphysics phenomenon that describes the interaction between a moving fluid and a deformable or movable structure. This work develops numerical-computational tools for FSI simulations, using the MFSim software in conjunction with external finite element models. The main goal was to create a methodology to couple structural models with fluid dynamics simulations, focusing on industrial applications such as the recovery boiler. The adopted approach involves the development of a mesh coupling algorithm and interpolating functions, allowing the association of structural and Lagrangian meshes for use in the immersed boundary method within a parallel execution environment. Additionally, a communication interface was created between MFSim and finite element software, such as Code_Aster and Salome-Meca, promoting the coupling of structural models with fluid dynamics simulations. The mesh association algorithm and interpolating functions were applied in a static structural analysis, where the immersed boundary followed the displacement field of the structure. A robustness test was also performed, where the structure underwent large-scale deformations, exceeding one meter. In both cases, the mesh association algorithm and interpolating functions were found to be robust. The numerical and computational tools were validated by comparing numerical results with experimental data available in the literature. The data coupling between MFSim and Salome-Meca was validated through the modal analysis of a pipe subjected to internal pressure and filled with oil. The developed computational tools were also applied in the modal analysis and fluidstructure interaction of a rectangular plate exposed to high temperatures. In all cases, the results showed good agreement with the literature, demonstrating the applicability of the developed approach. The results of this work indicate that the developed numerical and computational tools allow MFSim to utilize external finite element libraries, enabling the coupling of structural models with computational fluid dynamics tools for fluid-structure interaction analyses.